Case Report: Prolonged remission of metastatic cisplatin-refractory nasopharyngeal carcinoma with Pembrolizumab - Wang, Wei Cen; Preti, Beatrice; Read, Nancy; Gibson, Paul; Kwan, Keith; Winquist, Eric (Frontiers in Oncology, 2023)
Background: Epstein-Barr virus (EBV)-related nasopharyngeal cancer (NPC) is a common type of cancer in certain areas of the world such as southeast Asia, but is uncommon in Canada. There is currently no reliably effective standard treatment for incurable metastatic EBV-related NPC that progresses after first-line therapy with gemcitabine/cisplatin. Methods: With his consent, the health records of a patient with relapsed metastatic EBV-related NPC treated with pembrolizumab immunotherapy were retrospectively reviewed and reported. Case report: A male patient presented at age 15 with stage IVA EBV-related NPC. Despite response to initial chemoradiation and adjuvant chemotherapy, the patient experienced metastatic cancer relapse in lymph nodes and bone. There was initial response to gemcitabine/cisplatin chemotherapy, but the cancer progressed after 7 cycles. The patient was then switched to pembrolizumab and had a near complete clinical response after 14 cycles. Serum EBV titers have normalized and CT imaging shows only some healed bone metastasis. Retrospective assessment of tumor CPS PD-L1 was >20. Hypothyroidism developed, possibly due to radiation treatment, but otherwise he did not experience any other immune-mediated toxicities on or following treatment, which lasted in total 2 years with 41 cycles. To date, the patient has been observed off pembrolizumab for over one year and is highly functional without evidence of disease progression.2 This is a provisional file, not the final typeset article Conclusion: This case illustrates the potential benefit of immunotherapy for improving survival and quality of life in selected patients with metastatic EBV-positive cisplatin-refractory NPC.